Nasi Kemanusiaan (Nasi Sehat untuk Pasien Covid-19 yang Isolasi Mandiri) - Suwandi Suwandi; Widya Jati Lestari; Marsani Asfi (Jurnal Pemberdayaan Umat, 2022)
Purpose: to provide both moral and material assistance to Covid-19 positive patients who are self-isolating at home. With the assistance in the form of healthy rice for these patients, it will certainly provide their own motivation for the patients, so that they can quickly recover their condition. Method: The research method that the author uses is to begin with socializing fundraising, then handing over the donation funds to the Cirebon City Wani Amal Foundation office, then distributing 'humanitarian rice' or healthy rice for Covid-19 patients who are self-isolating. Result: The results of this study are the provision of healthy rice can run according to expectations, and get a positive response from the surrounding community. Conclusions: This humanitarian rice program (social activity) can help and ease the burden on COVID-19 patients who are self-isolating (isoman).